Pollen morphology and the relationships of Hoplestigmataceae - Nowicke, J. W.; Miller, J. S.
The pollen of the ditypic family Hoplestigmataceae was examined in LM, SEM, and TEM, and in conjunction with floral morphology compared with the orders Boraginales, Ebenales, and Violales, to which this family has been assigned. Hoplestigma has pollen with 3-colporate apertures bordered by (six)meridional ridges that are separated by (three)intercolpar concavities. Pollen similar in SEM and TEM is found in Bourreria and Ehretia of the Boraginaceae, and is also common in the Myrtales. However, this pollen type is not known to occur in either the Violales or Ebenales; in addition the bicarpellate ovary with few ovules and sympetalous corolla of Hoplestigma are not really typical of the Violales, nor is the parietal placentation of Hoplestigma typical of the Ebenales. Although Hoplestigma shares similar pollen, numerous stamens, and many characteristics of the gynoecium with the Myrtales, it differs in having the petals united basally and unitegmic ovules versus distinct petals and bitegmic ovules in Myrtales. Until Hoplestigmataceae is examined for the presence of internal phloem, one of the more definitive characters for Myrtales, we defer to Takhtajan's placement in the Boraginales.
Keywords: POLLEN; CONCAVITY; OVULES; STAMENS; PLANT MORPHOLOGY; PHLOEM; VASCULAR; PLANTS; TAXA; OVARIES; PLACENTATION